The influence of senior leaders on organisational learning: Insights from the employees' perspective. Issue 4 (September 2015) - Waddell, Alex; Pio, Edwina
In the current century, organisations are facing unprecedented changes in their working environments. In order to remain viable, organisations must learn to adapt to the changes they face. We investigate the influence of senior leaders on organisational learning from the employees' perspective. Data were based upon qualitative research utilising a case study of a New Zealand–operated information technology company. By employing an explorative, exploitative and transformative organisational learning framework, and a transactional and transformational model of leadership, the findings contribute empirically to the limited body of research surrounding how senior leaders influence organisational learning. In particular, the findings illustrate the way in which senior leaders employed a transformational leadership approach during explorative and transformative learning, while adopting a transactional leadership style during exploitative learning. Also compelling were participants' comments highlighting how senior leaders had employees emotionally connect and test business ideas and assumptions throughout the learning process.